The Effect of External Electric Field on The Electrical and Magnetic Properties of NiCl2 Monolayer with Density Functional Theory - Abdillah, M. A.; Suprayoga, E.; Prayitno, T. B. (MJI Publisher by PT Mitra Jurnal Indonesia, 2023)
The study utilized density functional theory (DFT) to investigate the impact of spin-orbit interaction and external electric fields on the NiCl2 monolayer. The results demonstrated a reduction in the energy band gap and a transition from an indirect semiconductor to a metal when different electric fields were applied. Additionally, the combination of external electric fields and spin-orbit interactions altered the band structure of the NiCl2 monolayer, leading to a transition from a semiconducting state to a metallic state. These findings have significant implications for spintronic device design, as they suggest the potential for controlling the electrical and magnetic properties of the NiCl2 monolayer, making it suitable for use in alternative spintronic devices.